Security Surveillance - Nirmal Das; Huma Jamshed , (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
Video surveillance systems are fundamental for monitoring public and private spaces, evolving from analog to IP cameras to meet increasing demands for intelligent features. However, managing large volumes of video streams poses challenges for human operators, leading to the adoption of intelligent systems integrating computer vision and artificial intelligence. These systems aim to replicate human visual perception while leveraging technological advantages. This paper explores the evolution and challenges of video surveillance, emphasizing the role of intelligent systems in enhancing security monitoring